2012
DOI: 10.2135/cropsci2012.01.0033
|View full text |Cite
|
Sign up to set email alerts
|

Wilt‐Based Irrigation in Kentucky Bluegrass: Effects on Visual Quality and Irrigation Amounts Among Cultivars

Abstract: 2012). Wilt-based irrigation in Kentucky bluegrass: Effects on visual quality and irrigation amounts among cultivars. Retrieved from http:/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
0
22
1
Order By: Relevance
“…Withholding irrigation until the 75% green stage is reached could save a significant amount of water in all bluegrasses, but particularly in those that retain green longer. In a previous study on these same plots, where irrigation was withheld until bluegrasses exhibited symptoms of drought stress, water savings were as high as 54% during summer months in cultivars that succumbed slower to drought stress (Lewis et al, 2012).…”
Section: Drought Responses Of Cultivarsmentioning
confidence: 98%
See 3 more Smart Citations
“…Withholding irrigation until the 75% green stage is reached could save a significant amount of water in all bluegrasses, but particularly in those that retain green longer. In a previous study on these same plots, where irrigation was withheld until bluegrasses exhibited symptoms of drought stress, water savings were as high as 54% during summer months in cultivars that succumbed slower to drought stress (Lewis et al, 2012).…”
Section: Drought Responses Of Cultivarsmentioning
confidence: 98%
“…1 and Fig. 2); these cultivars have previously performed well under reduced irrigation in Kansas (Lewis et al, 2012) and would be good choices for those interested in growing Kentucky bluegrass under such conditions. The performance of the two hybrid bluegrasses (Thermal Blue Blaze and Longhorn) was similar to the other KBG cultivars during the dry downs and recoveries, which is comparable to results from other research (Bremer et al, 2006;Su et al, 2007Su et al, , 2008Su et al, , 2009Richardson et al, 2008Richardson et al, , 2009).…”
Section: Drought Responses Of Cultivarsmentioning
confidence: 99%
See 2 more Smart Citations
“…The loss of turfgrass during severe droughts may result in unsatisfactory visual appearance and significant reestablishment and human labor costs. Previous studies have indicated that limited water applications during droughts may mitigate the severity of drought stress and improve Kansas State University Agricultural Experiment Station and Cooperative Extension Service the ability of turfgrass to recover upon rewatering (Lewis et al, 2012;Goldsby et al, 2015). This indicates a possible strategy to achieve a balance between water conservation and turfgrass survival through droughty periods.…”
Section: Rationalementioning
confidence: 99%